PENGEMBANGAN APLIKASI PERMOHONAN CUTI DENGAN METODE WATERFALL PADA PT AISIN INDONESIA AUTOMOTIVE BERBASIS WEB - Andre Ardiansyah; Sufajar Butsianto; Agus Suwarno (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
In an increasingly advanced digital era, the use of information technology has become an important need for industries and companies, including automotive manufacturing companies such as PT Aisin Indonesia Automotive. Currently, the application for leave of employees in such companies is still done verbally or through manual submission, which can take a long time and lead to clerical errors. Therefore, the development of a web-based leave application application is expected to increase the efficiency of the employee leave application process, facilitate access and approval, and reduce the potential for administrative errors. By using the Waterfall method, it is expected that each stage of application development will be carried out in a structured and systematic manner, so that it can provide real benefits for PT Aisin Indonesia Automotive in managing employee leave and applying modern information technology.